2017
DOI: 10.1007/s11010-017-3181-z
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented anticancer activities of organorhenium sulfonato and carboxylato complexes against hormone-dependent MCF-7 and hormone-independent triple-negative MDA-MB-231 breast cancer cells

Abstract: Cisplatin and other metal-based drugs often display side effects and tumor resistance after prolonged use. Because rhenium-based anticancer complexes are often less toxic, a novel series of organorhenium complexes were synthesized of the types: XRe(CO)Z (X = α-diimines and Z = p-toluenesulfonate, 1-naphthalenesulfonate, 2-naphthalenesulfonate, picolinate, nicotinate, aspirinate, naproxenate, flufenamate, ibuprofenate, mefenamate, tolfenamate, N-acetyl-tryptophanate), and their biological properties were examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…1. This study is designed to investigate the cell killing efficacy of PDT using our actively targeted nanoformulation (PLGA-PEG hTf BPD, referred to as "ANP") and compare it to both BPD in its free form (referred to as "free BPD") and passively targeted (PLGA-PEG BPD or "PNP") nanoparticles on TNBC cell line MDA-MB-231 (34)(35)(36)(37)(38)(39).…”
Section: Introductionmentioning
confidence: 99%
“…1. This study is designed to investigate the cell killing efficacy of PDT using our actively targeted nanoformulation (PLGA-PEG hTf BPD, referred to as "ANP") and compare it to both BPD in its free form (referred to as "free BPD") and passively targeted (PLGA-PEG BPD or "PNP") nanoparticles on TNBC cell line MDA-MB-231 (34)(35)(36)(37)(38)(39).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, a direct comparative results showing the difference in curcumin efficiency between non-malignant and cancer cells using folate decorated liposomes has not been demonstrated thus far. To test this comparison in vitro and challenge the selective attribute of curcumin when encapsulated in a targeted liposomal modality, we decided to conduct a parallel study using non-malignant mammary epithelial cells, MCF-12A, and triple negative breast cancer cells (TNBC), MDA-MB-231 [51,[59][60][61][62][63].…”
Section: Ivyspringmentioning
confidence: 99%
“…Organometallic rhenium compounds are strong anticancer agents. Sometimes the IC 50 values of many organometallic rhenium compounds against numerous cancer cells have been found to be in nM ranges [ 5 ]. We and others have demonstrated that organometallic rhenium compounds are not active on normal cells [ 5 - 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes the IC 50 values of many organometallic rhenium compounds against numerous cancer cells have been found to be in nM ranges [ 5 ]. We and others have demonstrated that organometallic rhenium compounds are not active on normal cells [ 5 - 8 ]. Many rhenium compounds have been found to be highly active on cancer cells resistant to chemo drugs [ 7 - 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation